Effective strategies at the ruck in men`s and women`s World Rugby Sevens Series - Barkell, J. F.; O`Connor, D.; Cotton, W. G. (International Journal of Sports Science & Coaching, 2018)
Despite the growth of research on rugby sevens since its inclusion into the 2016 Olympic Games, some performance aspects of the game remain in their infancy. The ruck is one such area that has had little examination. The aim of this research was to examine the relationships between ruck actions and ruck success. A series of men`s (N = 2521) and women`s (N = 1474) rucks were coded from a sample of men`s (N = 117) and women`s games (N = 65) played within the World Rugby Sevens Series in 2014. Both attacking and defensive ruck actions were analysed. Variables included player numbers in the ruck, the actions of the first players to the ruck, ball placement from the tackled player, the body height, weight distribution and position of the attacking player in the ruck. Chi squared analysis identified that one versus one rucks were most commonly formed. If an attacking player arrived first, then there was a greater chance of maintaining possession compared with the first arrival being from the defensive side (p < 0.001). Findings suggest that the squeeze ball placement technique is risky due to its association with turnovers and penalties against the attacking team in men`s rugby sevens (p < 0.001). The body position of the first arriving attacking player requires the attacking player to lower their shoulders below the opposition shoulders (p < 0.001), use the tackled player to support their weight (p < 0.001) and aim to ruck to a position past the ball rather than stopping with their bodies over the ball (p < 0.001). Analysis of opposition actions identified that an early jackal was most successful at producing turnovers (p < 0.001). Results illustrate successful ruck strategies in rugby sevens from both an attacking and a defensive viewpoint. Successful ruck actions are similar in both men`s and women`s rugby sevens. ABSTRACT FROM AUTHOR